Flowing Gold - Beach, Rex, 1877-1949 (Salt Lake City, UT : Project Gutenberg, 2004)
"Flowing Gold" by Rex Beach is a novel likely written in the late 19th century, during a time of American expansion and burgeoning industry. The story centers around Calvin Gray, a charming and resourceful man who arrives in Dallas amidst an oil boom, navigating a landscape full of opportunity and intrigue as he seeks to make a new start. The narrative explores themes of wealth, deception, and the human experience against the backdrop of a rapidly changing society fueled by the discovery of oil. The opening of "Flowing Gold" introduces Calvin Gray as he settles into his lavish accommodations at the Ajax Hotel in Dallas. He engages in witty exchanges with hotel staff, showcasing his charisma and hinting at his complex character. Gray's life as a "penniless adventurer" is rife with irony as he presents himself as a wealthy and important figure, all the while grappling with financial uncertainty. The story unfolds to reveal the stark contrast between his polished exterior and underlying desperation, as Gray embarks on a quest that intertwines his fate with the rapidly evolving world of Texas's oil industry. The introduction sets the stage for a thrilling adventure filled with potential betrayal, ambition, and the pursuit of fortune. (This is an automatically generated summary.)
Release date is 2004-09-01
Produced by Joshua Hutchinson, Charles Aldarondo and the Online Distributed Proofreading Team
Keywords: Petroleum industry and trade -- Texas -- Fiction; Texas -- History -- 20th century -- Fiction